2012
DOI: 10.1039/c2sc00866a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalyzed regiodivergent approach to macrolide motifs

Abstract: A strategy for regiochemical reversal of reductive macrocyclizations of aldehydes and terminal alkynes has been developed. Using an advanced synthetic intermediate directed towards the methymycin/neomethymycin class of macrolides, selective endocyclization provides the natural twelve-membered ring series, whereas ligand alteration enables selective exocyclization to provide access to the unnatural eleven-membered ring series. The twelve-membered ring adduct was converted to 10-deoxymethynolide, completing an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…42 Utilizing the inherent substrate biases of the terminal alkyne of 24 , the use of IMes ligand proved satisfactory in an endocyclization process to access product 25 in 58% yield as a 4:1 mixture of diastereomers with only endocyclization products being observed (Scheme 10). Alternatively, the unique properties of DP-IPr with terminal alkynes are illustrated by the highly selective exocyclization of the same substrate to afford 26 in 59% yield as a single regio- and stereoisomer.…”
Section: Mechanistic Insights Inform Regiodivergent Strategies In Nicmentioning
confidence: 99%
“…42 Utilizing the inherent substrate biases of the terminal alkyne of 24 , the use of IMes ligand proved satisfactory in an endocyclization process to access product 25 in 58% yield as a 4:1 mixture of diastereomers with only endocyclization products being observed (Scheme 10). Alternatively, the unique properties of DP-IPr with terminal alkynes are illustrated by the highly selective exocyclization of the same substrate to afford 26 in 59% yield as a single regio- and stereoisomer.…”
Section: Mechanistic Insights Inform Regiodivergent Strategies In Nicmentioning
confidence: 99%
“…[6,7] While both [1,3-bis(2,6-di-iso-propylphenyl)]-imidazolidin-2-ylidene (SIPr) and imidazol-2-ylidene (IPr) were effective ligands in the racemic tail-to-tail cross-hydroalkenylation, [7] the use of the corresponding NHC ligand rac-A1 led to a significant drop in reactivity (Table 1, entry 1). [8] We suspected the vicinal Ph groups to have an unfavorable steric effect, by pushing the N-aryl groups with their bulky isopropyl substituents in ortho position too close to the reaction center, thereby increasing the activation energy for the coordination of the substrate and lowering the reactivity. Further studies showed that both the size and the number of N-aryl ortho substituents played very important roles in determining the reactivity and selectivity of the hydroalkenylation (Table 1, entries 2-4).…”
mentioning
confidence: 99%
“…The optimized process has been subsequently applied to the preparation of modified macrolide structures. 243 In another example involving nickel, in this case as a co-catalyst, the use of mixtures of PEG 400 /MeOH as solvent enabled an intramolecular Glaser-Hay coupling 244 of simple terminal alkynes (140) to form 14-to 27-membered macrocyclic diynes (141,Scheme 11.18) to be conducted at comparatively high concentrations (up to 0.1 M). This was attributed to the aggregation properties of the PEG preferentially solubilizing the organic substrates, thus creating a phase separation from the copper-nickel catalyst system.…”
Section: Nickel-mediated Reactionsmentioning
confidence: 99%